Engineering pore ratio in hierarchical porous carbons towards high-rate and large-volumetric performances - Xu, Fei; Han, Haojie; Ding, Baichuan; Qiu, Yuqian; Zhang, En; Li, Hejun; Kaskel, Stefan (Microporous and Mesoporous Materials, 2019)
Hierarchical yet densely packed porous carbon electrodes are vital for achieving high-performance capacitive energy storage. However, hierarchical porous carbons (HPCs) suffer from a trade-off in terms of meso- and macroporosity ratio related to the pore size dependent diffusive ion mobility versus the material density dominating the volumetric performance. Here we report an interesting insight into a balanced effect of meso- and macroporosity ratio and the material density with a practical high mass loading by designing HPCs with controlled meso- and macroporosity ratio. This is achieved via a hypercrosslinking strategy of polystyrene without the assistant of any templates or activation. It is found that ion transport rates increase along with increasing the meso- and macropore content to 26% and then gradually level off even further increasing the amount to 73%. An appropriate meso- and macropore content without sacrificing the ion diffusivity is beneficial for achieving effective material densities up to 0.76 g cm−3, leading to superior volumetric capacitances, as compared with those showing either lower or higher meso- and macropore content. This study clearly highlights the need for fine-tuning the pore ratios at different scales in hierarchical structures to achieve high-performance applications for practical applications.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Hierarchical porous carbons; Hypercrosslinked polystyrene; Ion transport rate; Supercapacitors; Volumetric capacitance